IMPLEMENTASI PKPU NO.6 TAHUN 2020 DALAM PELAKSANAAN PILKADA TAHUN 2020 - Narayana, Putu Nandito; Erawan, I Ketut Putra; Erviantono, Tedi (Jurnal Nawala Politika, 2021)
This research is entitled "Implementation of Pkpu No. 6 of 2020 in the Implementation of the 2020 Regional Head Election (Case Study: KPU Badung Regency)". The purpose of this study is to find out how the implementation of PKPU No. 6 of 2020 on the implementation of the 2020 Badung district election. This study uses a qualitative descriptive method with Implementation Theory according to Merilee S. Grindle that the success of a public policy implementation according to Grindle, which consists of Content of Policy and Context of Policy. The results showed the implementation of PKPU No. 6 of 2020 had a lot of influence on the political climate, especially in Badung Regency. The implementation of PKPU No. 6 of 2020 according to Merilee S. Grindle's theory in the 2020 elections in Badung Regency has been implemented in accordance with the objectives of running democracy during the COVID-19 pandemic.   Keywords: Election of 2020, Pandemic Covid-19, Badung Regency